STUDI KARAKTERISTIK BATUAN MANIFESTASI PANAS BUMI DI SEKITAR GUNUNG TAMPUSU - Oliver Pongoh; Donny Royke Wenas; Theresje Mandang (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
North Sulawesi is one of the provinces in Indonesia which has many active volcanoes. Mount Tampusu is an area that has geothermal prospects characterized by geothermal manifestations on the surface, namely hot springs that can contribute to or influence the surrounding rocks making altered rocks within the scope of hot spring manifestations. This study aims to identify the mineral composition and type of alteration rock in the geothermal manifestation area around Mount Tampusu at the study site using SEM-EDX and FTIR methods to determine hydrothermal minerals present in these rocks. The results showed that the mineral composition of altered rock mineral in the geothermal manifestation in Tampusu Village, Remboken District had almost the same content between the rocks in the eyes of the hot springs (where the water came out) and those that were a few meters away from the manifestation, namely Al (Aluminum), Si ( Silica), S (Suklur). With the difference in elemental content, sample 2 has the addition of Al (Aluminum), Si (Silica), MoL (Molybdenum), K (Potassium), Fe (Ferum). And the types of altered rock minerals around the hot spring manifestations in rock samples 1 and 2 are Quartz, Montmonillonitre, Albite, Kaolinite, Gibbsite and Paligorskile.